2015
DOI: 10.4041/kjod.2015.45.5.253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the facial dimensions of young adult women with a preferred facial appearance

Abstract: ObjectiveThe aim of this study was to evaluate the facial dimensions of young adult women with a preferred facial appearance and compare the results with those from the general population.MethodsTwenty-five linear, nine angular, and three area measurements were made and four ratios were calculated using a sample of standardized frontal and lateral photographs of 46 young adult women with a preferred facial appearance (Miss Korea group) and 44 young adult women from the general population (control group). Diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 27 publications
(29 reference statements)
0
23
3
1
Order By: Relevance
“…However, the GP group in our study had a greater facial width than did the MK group, which was opposite to the results of Kim et al15 In addition, the facial height as well as the intercanthal and interpupillary widths, which showed significant intergroup differences in the study of Kim et al,15 showed no significant intergroup differences in our study. This might be attributed to the differences between the 2D and 3D nature of the studies and the associated difficulty in the identification of projected landmarks on 2D images.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the GP group in our study had a greater facial width than did the MK group, which was opposite to the results of Kim et al15 In addition, the facial height as well as the intercanthal and interpupillary widths, which showed significant intergroup differences in the study of Kim et al,15 showed no significant intergroup differences in our study. This might be attributed to the differences between the 2D and 3D nature of the studies and the associated difficulty in the identification of projected landmarks on 2D images.…”
Section: Discussioncontrasting
confidence: 99%
“…Kim et al15 evaluated the facial dimensions of young adult women with a preferred facial appearance. However, these studies were based on two-dimensional (2D) measurements taken using unstandardized photographs.…”
Section: Introductionmentioning
confidence: 99%
“…The authors conclude that attractive faces bear uniformity between different facial sub-regions. Kim et al [15], evaluated the facial appearance of young women against a preferred face appearance and compared the results with the general population. Zhuang et al [16] evaluated the facial anthropometric variations across age groups, gender and race for face images.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In facial soft tissues, the lip vermilion is a prominent feature due to its obvious soft tissue contours compared with facial skin [7]. Several studies have explored the general 3D facial structures of Asian adult female patients and highlighted signi cant morphological in uences on the lip vermilion in patients who were considered more attractive than those who were considered average [7,8]. Several studies have demonstrated signi cant differences in lip vermilion curvature and shape during orthodontic treatment using 3D facial scanning [9,10].…”
Section: Introductionmentioning
confidence: 99%